African Ethnobotany in the Americas - Zent, Egleé L. (Ethnobiology Letters, 2013)
Review of African Ethnobotany in the Americas. Edited by Robert Voeks and John Rashford. 2013. Springer. Pp. 429, 105 illustrations, 69 color illustrations. 49.95 (paperback). ISBN 978‐1461408352.